Near-infrared light responsive nanomaterial and preparation method and application thereof
Patent Information
- Application Number
- CN202410675860.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-28
AI Technical Summary
然而,上述方法往往需要长时间的作用才能杀灭细菌,这不可避免地会在重复的抗菌过程中导致细菌耐药性的形成
[0028]1.本申请制备得到的近红外光响应型纳米材料,以具有近红外(NIR)光吸收和类过氧化物酶(POD)催化活性的Au NBPs双锥颗粒为基材,通过化学还原法将铂(Pt)纳米粒修饰到Au NBPs双锥颗粒的尖端上,一方面促进Au NBPs双锥颗粒在NIR区的吸收峰从近红外一区(NIR-I)红移至近红外二区(NIR-II),另一方面还能促进Au NBPs双锥颗粒的电子转移,从而提高了光热治疗和纳米酶催化治疗的效果;
Smart Images

Figure CN118527647B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanomaterials, specifically to a near-infrared light-responsive nanomaterial, its preparation method, and its applications. Background Technology
[0002] Titanium (Ti) and its alloys are among the most commonly used orthopedic implant materials due to their low density, low elastic modulus, high strength, excellent biocompatibility, and corrosion resistance. However, titanium implant failures are common due to issues such as bacterial infection on the implant surface, bacterial biofilm formation, and insufficient osseointegration. Currently, the general design strategy for antibacterial implants involves constructing functional materials on the titanium implant surface to enhance the antibacterial properties of the biomaterial itself. This can be achieved through drug loading, altering surface charge, releasing bactericidal particles, or modifying the electrostatic repulsion and superhydrophobicity of the material surface to resist bacterial adhesion. However, these methods often require prolonged exposure to kill bacteria, inevitably leading to the development of drug resistance during repeated antibacterial treatments. Therefore, there is an urgent need to develop new methods to rapidly and efficiently eliminate implant-related infections.
[0003] Therefore, this application provides a near-infrared light-responsive nanomaterial, its preparation method, and its application. Summary of the Invention
[0004] To overcome the shortcomings of existing technologies, this invention provides a near-infrared light-responsive nanomaterial, its preparation method, and its application. In the nanomaterial, gold nanobipyramidal particles (Au NBPs) with near-infrared (NIR) light absorption and peroxidase-like (POD) catalytic activity are used as the substrate. Platinum (Pt) nanoparticles are modified onto the tips of Au NBPs by chemical reduction. This promotes the redshift of the absorption peak of Au NBPs in the NIR region from the near-infrared I region (NIR-I) to the near-infrared II region (NIR-II). It also promotes electron transfer in Au NBPs, thereby improving the effects of photothermal therapy and nanozyme catalytic therapy.
[0005] The technical solution adopted by this invention to solve its technical problem is:
[0006] The primary objective of this application is to provide a near-infrared light-responsive nanomaterial, wherein the nanomaterial is a gold nanobipyramidal structure with platinum nanoparticles loaded at one or both ends.
[0007] Furthermore, the gold nanobipyramidal structure has a major axis of 115.02±11.4 nm and a diameter of 26.35±4.12 nm.
[0008] Furthermore, the particle size of the platinum nanoparticles is 2.76 ± 0.23 nm.
[0009] This invention also provides a method for preparing near-infrared light-responsive nanomaterials, the method comprising the following steps:
[0010] (1) Add 0.08-1.0 mol / mL chloroauric acid solution and 0.04-0.06 mol / mL trisodium citrate aqueous solution to 9-10 mL of deionized water. Under magnetic stirring, quickly add 0.06-0.08 mol / mL frozen sodium borohydride solution and continue stirring for 15-30 s until the solution turns pink. Then let it stand at room temperature for 1.5-3 h to obtain gold nano bipyramidal seed solution.
[0011] (2) Mix 2.0-3.0 mmol / mL hexadecyltrimethylammonium bromide solution, 4-6 mmol / mL chloroauric acid solution, 20-25 mmol / mL silver nitrate solution, 1.0-1.5 mol / mL dilute hydrochloric acid, and 0.30-0.35 mol / mL L-ascorbic acid solution evenly, then add 0.2-0.4 mL of the gold nanoparticle seed solution obtained in step (1), shake well for 10-15 s, and let stand at room temperature for 12-14 h to obtain a crude solution of gold nanoparticles;
[0012] (3) Centrifuge the crude gold nanoparticle bipyramidal solution at 9000–9500 rpm for 10–15 min, discard the supernatant, and redisperse the precipitate in 0.20–0.30 mmol / mL hexadecyltrimethylammonium chloride solution. Then, add 1.50–1.70 mmol / mL silver nitrate solution and 3.0–3.5 mmol / mL L-ascorbic acid solution sequentially and mix well. Heat the reaction solution in a water bath at 60–70 °C for 4–5 h. After the reaction is complete, centrifuge the reaction solution at 5000–6000 rpm for 10–15 min, discard the supernatant, and redisperse the lower precipitate. Dispersed in a 0.20–0.30 mmol / mL hexadecyltrimethylammonium bromide solution, the mixture was allowed to stand in a water bath at 25–30 °C for 4–5 h. The supernatant was then gently poured off, leaving the precipitate at the bottom. The precipitate was dispersed in 100–120 mL of deionized water. 10–15 mL of concentrated hydrogen peroxide and 10–15 mL of concentrated ammonia were added sequentially. After shaking for 30–35 s, the solution became clear. Then, a 0.01–0.2 mol / mL hexadecyltrimethylammonium bromide solution was added. After mixing, the mixture was centrifuged at 9000–9500 rpm for 10–15 min and washed to obtain homogeneous gold nanobipyramidal nanoparticles.
[0013] (4) Take 0.01-0.02 mol / mL of the gold nanoparticles obtained in step (3) and disperse them in a 0.04-0.06 mol / mL solution of hexadecyltrimethylammonium chloride. Then add 1-2 mol / mL of silver nitrate and 20-25 mol / mL of ascorbic acid solution to obtain a mixed solution. Place the mixed solution in a constant temperature air shaker at 60-70℃ and 100-150 rpm and react for 4-6 hours. Then centrifuge at 6000-7000 rpm. Centrifuge for 10–15 min; the resulting precipitate is redispersed in a 1.0–2.0 mmol / mL cetyltrimethylammonium bromide solution, followed by the addition of 50–60 μL of a solution containing 0.05–1 mM chloroplatinic acid and 0.01–0.02 M L-ascorbic acid. The mixture is allowed to stand at room temperature for 10–14 h, followed by centrifugation at 3500–5000 rpm for 10–15 min. The resulting precipitate is then redispersed in water for storage, yielding Pt-loaded gold nanobipyramidal nanoparticles.
[0014] Furthermore, the preparation method of the gold nanobipyramidal structure includes the following steps:
[0015] (1) Add 0.08 mol / mL chloroauric acid solution and 0.04 mol / mL trisodium citrate aqueous solution to 9 mL of deionized water. Under magnetic stirring at 1200 rpm, quickly add 0.07 mol / mL frozen sodium borohydride solution and continue stirring for 15 s until the solution turns pink. Then let it stand at room temperature for 2 h to obtain gold nano bipyramidal seed solution.
[0016] (2) Mix 2.5 mmol / mL hexadecyltrimethylammonium bromide solution with 5 mmol / mL chloroauric acid solution with 25 mmol / mL silver nitrate solution, 1.25 mol / mL dilute hydrochloric acid, and 0.31 mol / mL L-ascorbic acid solution evenly, then add 0.2 mL of the gold nano bipyramidal seed solution obtained in step (1), shake well for 10 s, and let stand at room temperature for 12 h to obtain a crude solution of gold nano bipyramidals.
[0017] (3) Centrifuge the crude gold nanoparticle bipyramidal solution at 9000 rpm for 10 min, discard the supernatant, and redisperse the precipitate in 0.27 mmol / mL hexadecyltrimethylammonium chloride solution. Then, add 1.67 mmol / mL silver nitrate solution and 3.33 mmol / mL L-ascorbic acid solution sequentially and mix well. Heat the reaction solution in a 65℃ water bath for 4 h. After the reaction is complete, centrifuge the reaction solution at 5000 rpm for 10 min, discard the supernatant, and redisperse the lower precipitate. The gold nanoparticles were dispersed in a 0.25 mmol / mL hexadecyltrimethylammonium bromide solution and allowed to stand in a 30°C water bath for 4 hours. The supernatant was then gently poured off, leaving the precipitate at the bottom. The precipitate was dispersed in 100 mL of deionized water. 10 mL of concentrated hydrogen peroxide and 10 mL of concentrated ammonia were added sequentially, and the mixture was shaken for 30 seconds until the solution became clear. Then, 0.01 mol / mL hexadecyltrimethylammonium bromide solution was added, and the mixture was centrifuged at 9000 rpm for 10 min. After washing, uniform gold nanoparticles were obtained.
[0018] (4) Take 0.01 mol / mL of the gold nanobipyramid obtained in step (3) and disperse it in a 0.04 mol / mL hexadecyltrimethylammonium chloride solution. Then add 1 mol / mL silver nitrate and 20 mol / mL ascorbic acid solution to obtain a mixed solution. Place the mixed solution in a constant temperature air shaker at 60℃ and 100 rpm and react for 4.5 h. Then centrifuge at 6000 rpm for 10 min. The obtained precipitate is redispersed in a 1.5 mmol / mL hexadecyltrimethylammonium bromide solution. Then add 50 μl of a solution containing 1 mM chloroplatinic acid and 0.01 M L-ascorbic acid. Let it stand at room temperature for 12 h. Then centrifuge at 3500-5000 rpm for 10 min. The obtained precipitate is redispersed in water for storage to obtain Pt-loaded gold nanobipyramid.
[0019] The present invention also provides the use of the nanomaterials in the preparation of implant materials with antibacterial and bone-repair-promoting properties.
[0020] Furthermore, the method for preparing the implant material includes the following steps:
[0021] (1) Prepare a dispersion of gold nanobipyramidal loaded with Pt at a concentration of 4-6 mg / mL. Drop 50-60 μL of the dispersion onto pure titanium. Then rotate at 1000-1500 rpm for 3-5 s and then at 3000-3500 rpm for 25-30 s to complete one film deposition. Repeat the process 4-6 times at the same speed. After rinsing with deionized water multiple times, vacuum dry to obtain Ti / Au / Pt material.
[0022] (2) Soak Ti / Au / Pt in 1.5-2.5 mg / mL RGDC peptide solution at room temperature for 10-14 h, then rinse repeatedly with deionized water to remove unreacted RGDC peptide solution, and dry to obtain the final product.
[0023] Furthermore, the method for preparing the implant material includes the following steps:
[0024] (1) Prepare a dispersion of gold nanobipyramidal loaded with Pt at a concentration of 5 mg / mL. Drop 50 μL of the dispersion onto pure titanium and then rotate at 1000 rpm for 3 s and 3000 rpm for 30 s to complete one film deposition. Repeat the process 5 times with the same rotation speed. After rinsing with deionized water multiple times, vacuum dry to obtain Ti / Au / Pt material.
[0025] (2) Soak Ti / Au / Pt in a 2 mg / mL RGDC peptide solution at room temperature for 12 h, then rinse repeatedly with deionized water to remove unreacted RGDC peptide solution, and dry to obtain the final product.
[0026] This application focuses on the two main causes of orthopedic implant failure (bacterial infection and insufficient osseointegration). Combining photothermal therapy with a nanozyme catalytic therapy system, a NIR-responsive Au / Pt / RGDC nanomaterial is constructed for implant antibacterial and bone-promoting treatment. The Au / Pt / RGDC nanomaterial achieves rapid and efficient bactericidal effects under NIR irradiation through photothermal therapy combined with nanozyme catalytic therapy. Its bactericidal mechanism is as follows: while generating a photothermal effect for bactericidal action, the increased local temperature accelerates the consumption of glutathione (GSH) and enhances its POD-like activity, thereby enhancing the nanozyme catalytic effect. Simultaneously, the nanozyme catalyzes H2O2 to produce ·OH, which cleaves the eDNA on the biomembrane, eliminating the biomembrane, and also accelerates the oxidation of phospholipids and proteins on the cell membrane, making bacteria highly sensitive to local high temperatures, thus enhancing the photothermal effect. Ultimately, in a bacterial infection microenvironment, Ti / Au / Pt / RGDC implants with Au / Pt / RGDC nanomaterials can rapidly and efficiently kill bacteria and promote bone formation after NIR irradiation.
[0027] The beneficial effects of this invention are:
[0028] 1. The near-infrared photoresponsive nanomaterial prepared in this application uses Au NBPs bipyramidal particles with near-infrared (NIR) light absorption and peroxidase-like (POD) catalytic activity as the substrate. Platinum (Pt) nanoparticles are modified onto the tips of the Au NBPs bipyramidal particles by chemical reduction. On the one hand, this promotes the red shift of the absorption peak of the Au NBPs bipyramidal particles in the NIR region from the near-infrared I region (NIR-I) to the near-infrared II region (NIR-II). On the other hand, it also promotes electron transfer in the Au NBPs bipyramidal particles, thereby improving the effects of photothermal therapy and nanozyme catalytic therapy.
[0029] 2. In the application of the Ti / Au / Pt / RGDC nanomaterials, the modification with RGDC peptides not only improves the biocompatibility of the material but also promotes the adhesion, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Under NIR irradiation, the Au / Pt / RGDC nanomaterials achieve a rapid and efficient bactericidal effect through photothermal therapy combined with nanozyme catalytic therapy. Attached Figure Description
[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0031] Figure 1 This is a schematic diagram illustrating the principle of the synthesis of the nanomaterials described in this application;
[0032] Figure 2 Characterization diagram of the gold nanobipyramidal structure described in this application;
[0033] Figure 3 Characterization diagram of the ePt-Au NBPs applied for;
[0034] Figure 4 To simulate the electric field distribution of gold nanorods and gold nanobipyramids using FDTD;
[0035] Figure 5 To simulate the electric field distribution of aPt-Au NBPs and ePt-Au NBPs using FDTD;
[0036] Figure 6 Scanning electron microscope (SEM) images of Ti / Au / Pt / RGDC;
[0037] Figure 7 Evaluation of photothermal properties and peroxidase activity of Ti / Au / Pt / RGDC; (A) Photothermal properties; (B) Peroxidase activity;
[0038] Figure 8To evaluate the in vitro antibacterial activity of Ti / Au / Pt / RGDC; where: (A) bacterial survival rate after treatment under different conditions; (B) quantification of biofilm biomass after treatment under different conditions; (1) Ti, (2) Ti+H2O2, (3) Ti / Au / Pt / RGDC, (4) Ti / Au / Pt / RGDC+H2O2 (*p<0.05, **p<0.01 and ***<0.001);
[0039] Figure 9 The evaluation materials used in this application serve as indicators for promoting mesenchymal stem cell adhesion, proliferation, and osteogenic differentiation.
[0040] Figure 10 To evaluate the antibacterial and osteointegration capabilities of Ti / Au / Pt / RGDC in vivo and in vitro;
[0041] (A) Bacterial survival rate of Ti and Ti / Au / Pt / RGDC implants; (B) Quantitative analysis of new bone formation in toluidine blue stained images. (*p<0.05, **p<0.01, ***<0.001). Detailed Implementation
[0042] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.
[0043] Example 1
[0044] The method for preparing Ti / Au / Pt / RGDC samples includes the following steps:
[0045] (1) Preparation of seed solution of gold nanobipyramidal (Au NBPs)
[0046] Add 0.01M, 0.125mL chloroauric acid solution and 0.01M, 0.25mL trisodium citrate aqueous solution to 9.625mL deionized water. Under magnetic stirring at 1200rpm, rapidly add 0.01M, 0.15mL frozen sodium borohydride solution and continue stirring for 15s until the solution turns pink. Then let it stand at room temperature for 2h to obtain gold nanoparticle bipyramidal seed solution.
[0047] (2) Preparation of crude gold nanobipyramidal particles (AuNBPs)
[0048] Mix 0.1M, 40mL hexadecyltrimethylammonium bromide solution with 0.01M, 2.0mL chloroauric acid solution and 0.01M, 0.4mL silver nitrate solution, 1.0M, 0.8mL dilute hydrochloric acid, and 0.1M, 0.32mL L-ascorbic acid solution until homogeneous. Then add 0.2mL of the gold nanoparticle seed solution obtained in step (1), shake well for 10s, and let stand at room temperature for 12h to obtain a crude solution of gold nanoparticles.
[0049] (3) Purification of gold nanobipyramidal (Au NBPs)
[0050] Centrifuge the crude gold nanoparticle biconical solution at 9000 rpm for 10 min, discard the supernatant, and redisperse the precipitate in 300 mL of 0.08 M hexadecyltrimethylammonium chloride solution. Then add 6 mL of 0.01 M silver nitrate solution and 3 mL of 0.1 M L-ascorbic acid solution and mix well. Heat the reaction solution in a water bath at 65 °C for 4 h.
[0051] After the reaction is complete, the reaction solution is centrifuged at 5000 rpm for 10 min, the supernatant is discarded, and the lower precipitate is redispersed in 0.05 M, 200 mL of cetyltrimethylammonium bromide solution. The solution is allowed to stand in a 30 °C water bath for 4 h. Then the supernatant is gently discarded, leaving the bottom precipitate, and the precipitate is dispersed in 100 mL of deionized water.
[0052] 10 mL of concentrated hydrogen peroxide and 10 mL of concentrated ammonia were added sequentially. After shaking for 30 seconds, the solution became clear. Then, 5 mL of 0.05 M hexadecyltrimethylammonium bromide solution was added. After mixing, the solution was centrifuged at 9000 rpm for 10 min and washed to obtain uniform gold nanobipyramidal (Au NBPs).
[0053] (4) Preparation of Pt-loaded gold nanobipyramidal (ePt-Au NBPs)
[0054] Take 0.02M, 2mL of the gold nanobipyramid obtained in step (3) and disperse it in 0.08M, 2mL of hexadecyltrimethylammonium chloride solution. Then add 0.01M, 10μL of silver nitrate solution and 0.1M, 5μL of ascorbic acid solution to obtain a mixed solution. Place the mixed solution in a constant temperature air shaker at 60℃ and 100rpm and react for 4.5h. Then centrifuge at 6000rpm for 10min. The obtained precipitate is redispersed in 0.003M, 2mL of hexadecyltrimethylammonium bromide solution. Then add 50μl of a solution containing 1mM chloroplatinic acid and 0.01M L-ascorbic acid. Let it stand at room temperature for 12h. Then centrifuge at 3500-5000rpm for 10min. The obtained precipitate is redispersed in 2mL of water for storage, thus obtaining Pt-loaded gold nanobipyramids (ePt-Au NBPs).
[0055] (5) Preparation of Ti / Au / RGDC materials and Ti / Au / Pt / RGDC materials
[0056] The titanium sheet was continuously polished with sandpaper of different grits until the surface became smooth. Then, the polished titanium sheet was ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 15 minutes each, and dried for later use.
[0057] A 5 mg / mL Au NBPs dispersion and an ePt-Au NBPs dispersion were prepared. The spin coater was placed in a clean bench, and a 1.1 × 1.1 × 0.2 cm pure titanium sample was placed on the spin coater. 50 μL of Au NBPs dispersion and ePt-AuNBPs dispersion were dropped onto the sample, respectively. The spin coater was then rotated at 1000 rpm for 3 s and then at 3000 rpm for 30 s to complete one layer of film deposition. The same rotation speed was then used to repeat the process 5 times. After rinsing with deionized water multiple times, the samples were vacuum dried to obtain Ti / Au materials and Ti / Au / Pt materials, respectively.
[0058] Ti / Au and Ti / Au / Pt were immersed in a 2 mg / mL RGDC peptide solution at room temperature for 12 h. After immersion, they were repeatedly rinsed with deionized water to remove unreacted RGDC peptide solution and dried to obtain Ti / Au / RGDC material and Ti / Au / Pt / RGDC material, respectively.
[0059] Synthesis and characterization of ePt-Au NBPs
[0060] TEM results showed that Au NBPs had a bipyramidal structure with a major axis of 115.02 ± 11.4 nm and a diameter of 26.35 ± 4.12 nm. After the synthesis of Au NBPs, a thin Ag layer was grown on their surface to promote the selective deposition of Pt nanoparticles at the tips of Au NBPs. TEM results showed that Pt nanoparticles (2.76 ± 0.23 nm) were mainly deposited at the tips of Au NBPs in the ePt-Au NBPs structure. The microstructure and elemental distribution of ePt-Au NBPs were further verified by HAADF-STEM imaging and elemental line scanning. The line scanning results were in good agreement with the morphology results, indicating that Pt nanoparticles were mainly deposited at the tips of Au NBPs. HRTEM images of Au NBPs showed crystal planes with lattice spacing of 0.235 nm and 0.201 nm, which corresponded well to the characteristic (111) and (200) crystal planes of Au. HRTEM images of ePt-Au NBPs revealed a crystal plane with a lattice spacing of 0.224 nm, which corresponds well to the characteristic (111) crystal plane of Pt. The XRD patterns of Au NBPs corresponded to the three characteristic diffraction peaks of Au (38.2°, 44.3°, and 64.6°), while the XRD patterns of ePt-Au NBPs showed both the three characteristic diffraction peaks of Au and the two characteristic diffraction peaks of Pt at 39.9° and 46.5°. The zeta potentials of Au NBPs and ePt-Au NBPs were 19.57±1.62 and 39.73±1.45, respectively. The optical properties of Au NBPs and ePt-Au NBPs were then investigated using UV-Vis spectroscopy. Au NBPs exhibited a strong LSPR peak at 839 nm and a weaker transverse peak at 525 nm. After Pt nanoparticles are deposited on top of Au NBPs, the LSPR peak of ePt-Au NBPs redshifts to 1050 nm in the near-infrared II region, while the lateral peaks show almost no shift. Compared to the near-infrared I window (750–900 nm, NIR-I), the near-infrared II window (1000–1700 nm, NIR-II) offers stronger tissue penetration and a higher maximum permissible laser irradiation intensity, making it a more ideal choice for light sources.
[0061] FDTD simulation
[0062] The computational simulations were performed using the finite-difference time-domain (FDTD) method, with perfectly matched layers (PML) as the boundary condition, and the boundary condition was obtained from FDTD Solutions (Lumerical, Canada). The optical constants of Au were taken from gold as measured by Johnson and Christy. The size of the Au NBPs was matched to the average value. For the ePt-Au NBPs model, Pt particles were located at both ends of the Au NBPs. Results are shown in […]. Figure 4 and Figure 5 . Figure 4 The electric field distribution of gold nanorods and Au NBPs was simulated using FDTD. Figure 5 The electric field distribution of aPt-Au NBPs and ePt-Au NBPs was simulated using FDTD.
[0063] Photothermal properties and peroxidase activity detection
[0064] Different materials were placed in 24-well culture plates, and 1 mL of PBS solution was added. The samples were continuously irradiated for 15 minutes using a 0.6 W cm⁻², 1064 nm laser. The photothermal performance of different implants was evaluated by temperature rise curves and thermal imaging. 50 μL (20 mM) TMB solution, 50 μL (0.1 M) H₂O₂ solution, and 0.9 mL NaAc-HAc buffer solution were added to the surface of different materials. After 15 min of reaction, the absorbance of the reaction solution at 652 nm was measured using UV-Vis. Subsequently, the temperature, pH, and light intensity were adjusted to investigate the POD-like catalytic activity of the Ti / Au / Pt / RGDC samples. Furthermore, a cyclic irradiation experiment of Ti / Au / Pt / RGDC with NIR was conducted. After 5 cycles of continuous irradiation and cooling, the temperature rise and catalytic activity changes of ePt-Au NBPs were observed. Results are shown below. Figure 7 .
[0065] In vitro antibacterial and anti-biofilm evaluation
[0066] The antibacterial test of the material was conducted using Staphylococcus aureus. The bacteria were cultured in LB liquid medium. 500 μL of the bacterial suspension (1 × 10⁻⁶) was... 6 CFU / mL was added to the surface of different samples in a 24-well plate. Experimental groups: (1) Ti, (2) Ti + H2O2, (3) Ti / Au / Pt / RGDC, (4) Ti / Au / Pt / RGDC + H2O2, (5) NIR + Ti, (6) NIR + Ti + H2O2, (7) NIR + Ti / Au / Pt / RGDC, (8) NIR + Ti / Au / Pt / RGDC + H2O2, (9) NIR + Ti / Au / Pt / RGDC + H2O2 + hypoxia. The near-infrared laser power was 0.6 W / cm². -2 The irradiation time was 15 minutes. Specific antibacterial evaluations included plate plating, bacterial viability staining, and SEM observation. 500 μL of bacterial suspension (1 × 10⁻⁶) was used. 6CFU / mL was added to the surface of different samples and incubated at 37°C for 48 hours, with the culture medium changed every 12 hours, to allow bacterial biofilm to grow on the sample surface. Experimental grouping and treatment were the same as in the antibacterial experiment; specific evaluation of anti-biofilm activity included crystal violet staining and bacterial live / dead staining. After the treated bacterial suspension was thoroughly mixed, 20 μL of the suspension was taken, diluted 100-fold with LB liquid medium, and then 100 μL was evenly spread onto LB solid medium plates. After incubation at 37°C for 24 hours, the number of colonies was counted. The viability of bacteria on different samples was detected using a live / dead bacteria double staining kit. Bacteria or biofilms were stained with STYO9 and PI staining solutions in the dark for 30 minutes. Excess staining solution in the reaction system was then washed away with sterile phosphate-buffered saline (PBS), and the samples were observed and photographed under a confocal laser scanning microscope (CLSM). Bacteria from different groups were centrifuged and fixed with paraformaldehyde solution at 4°C for 30 minutes. The bacteria were dehydrated using gradient ethanol solutions (20%, 40%, 60%, 80%, and 100%) for 15 min each, followed by dehydration with tert-butanol for 30 min. Finally, the dehydrated bacteria were dried, sprayed with gold, and observed using SEM.
[0067] The biofilm was stained with 1 mL of 0.2% crystal violet solution. After standing at room temperature for 30 min, it was washed three times with sterile PBS buffer to remove unbound crystal violet, and then photographed for observation. After photographing, 1 mL of 100% ethanol was added to dissolve the crystal violet dye, and the residual amount of biofilm was assessed by measuring the absorbance of the resulting solution at 590 nm using a microplate reader. Results are shown below. Figure 8 .
[0068] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.
Claims
1. The use of nanomaterials in the preparation of implant materials with antibacterial and bone-repair-promoting properties, characterized in that, The nanomaterial is a gold nanobipyramidal structure with platinum nanoparticles loaded at one or both ends. The major axis of the gold nanobipyramidal structure is 115.02±11.4 nm, and the diameter is 26.35±4.12 nm. The preparation method of the implant material is as follows: (1) Prepare a dispersion of gold nanobipyramidal loaded with Pt at a concentration of 4-6 mg / mL. Drop 50-60 μL of the dispersion onto pure titanium. Then rotate at 1000-1500 rpm for 3-5 s and 3000-3500 rpm for 25-30 s to complete one film deposition. Repeat the process 4-6 times at the same speed. After rinsing with deionized water multiple times, vacuum dry to obtain Ti / Au / Pt material. (2) Soak Ti / Au / Pt in 1.5-2.5 mg / mL RGDC peptide solution at room temperature for 10-14 h, then rinse repeatedly with deionized water to remove unreacted RGDC peptide solution, and dry to obtain the final product.
2. The use according to claim 1, characterized in that, The method for preparing the implant material includes the following steps: (1) Add 0.08-1.0 mol / mL chloroauric acid solution and 0.04-0.06 mol / mL trisodium citrate aqueous solution to 9-10 mL of deionized water. Under magnetic stirring, quickly add 0.06-0.08 mol / mL frozen sodium borohydride solution and continue stirring for 15-30 s until the solution turns pink. Then let it stand at room temperature for 1.5-3 h to obtain gold nano bipyramidal seed solution. (2) Mix 2.0-3.0 mmol / mL hexadecyltrimethylammonium bromide solution, 4-6 mmol / mL chloroauric acid solution, 20-25 mmol / mL silver nitrate solution, 1.0-1.5 mol / mL dilute hydrochloric acid, and 0.30-0.35 mol / mL L-ascorbic acid solution evenly, then add 0.2-0.4 mL of the gold nanoparticle seed solution obtained in step (1), shake well for 10-15 s, and let stand at room temperature for 12-14 h to obtain a crude solution of gold nanoparticles; (3) Centrifuge the crude gold nanoparticle bipyramidal solution at 9000–9500 rpm for 10–15 min, discard the supernatant, and redisperse the precipitate in 0.20–0.30 mmol / mL hexadecyltrimethylammonium chloride solution. Then, add 1.50–1.70 mmol / mL silver nitrate solution and 3.0–3.5 mmol / mL L-ascorbic acid solution sequentially and mix well. Heat the reaction solution in a water bath at 60–70 °C for 4–5 h. After the reaction is complete, centrifuge the reaction solution at 5000–6000 rpm for 10–15 min, discard the supernatant, and redisperse the lower precipitate. Dispersed in a 0.20–0.30 mmol / mL hexadecyltrimethylammonium bromide solution, the mixture was allowed to stand in a water bath at 25–30 °C for 4–5 h. The supernatant was then gently poured off, leaving the precipitate at the bottom. The precipitate was dispersed in 100–120 mL of deionized water. 10–15 mL of concentrated hydrogen peroxide and 10–15 mL of concentrated ammonia were added sequentially. After shaking for 30–35 s, the solution became clear. Then, a 0.01–0.2 mol / mL hexadecyltrimethylammonium bromide solution was added. After mixing, the mixture was centrifuged at 9000–9500 rpm for 10–15 min and washed to obtain homogeneous gold nanobipyramidal nanoparticles. (4) Take 0.01-0.02 mol / mL of the gold nanoparticles obtained in step (3) and disperse them in a 0.04-0.06 mol / mL solution of hexadecyltrimethylammonium chloride. Then add 1-2 mol / mL of silver nitrate and 20-25 mol / mL of ascorbic acid solution to obtain a mixed solution. Place the mixed solution in a constant temperature air shaker at 60-70℃ and 100-150 rpm and react for 4-6 hours. Then centrifuge at 6000-7000 rpm. Centrifuge for 10–15 min; the resulting precipitate is redispersed in a 1.0–2.0 mmol / mL hexadecyltrimethylammonium bromide solution, followed by the addition of 50–60 μL of a solution containing 0.05–1 mM chloroplatinic acid and 0.01–0.02 M L-ascorbic acid. The mixture is allowed to stand at room temperature for 10–14 h, followed by centrifugation at 3500–5000 rpm for 10–15 min. The resulting precipitate is then redispersed in water for storage, yielding Pt-loaded gold nanobipyramidal nanoparticles. (5) Prepare a dispersion of gold nanobipyramidal loaded with Pt at a concentration of 4-6 mg / mL. Drop 50-60 μL of the dispersion onto pure titanium. Then rotate at 1000-1500 rpm for 3-5 s and then at 3000-3500 rpm for 25-30 s to complete one film deposition. Repeat the process 4-6 times at the same speed. After rinsing with deionized water multiple times, vacuum dry to obtain Ti / Au / Pt material. (6) Soak Ti / Au / Pt in 1.5-2.5 mg / mL RGDC peptide solution at room temperature for 10-14 h, then rinse repeatedly with deionized water to remove unreacted RGDC peptide solution, and dry to obtain the final product.
3. The use according to claim 2, characterized in that, The method for preparing the implant material includes the following steps: (1) Add 0.08 mol / mL chloroauric acid solution and 0.04 mol / mL trisodium citrate aqueous solution to 9 mL of deionized water. Under magnetic stirring at 1200 rpm, quickly add 0.07 mol / mL frozen sodium borohydride solution and continue stirring for 15 s until the solution turns pink. Then let it stand at room temperature for 2 h to obtain gold nano bipyramidal seed solution. (2) Mix 2.5 mmol / mL hexadecyltrimethylammonium bromide solution, 5 mmol / mL chloroauric acid solution, 25 mmol / mL silver nitrate solution, 1.25 mol / mL dilute hydrochloric acid and 0.31 mol / mL L-ascorbic acid solution evenly, then add 0.2 mL of the gold nano bipyramidal seed solution obtained in step (1), shake well for 10 s, and let stand at room temperature for 12 h to obtain a crude solution of gold nano bipyramidals. (3) Centrifuge the crude gold nanoparticle bipyramidal solution at 9000 rpm for 10 min, discard the supernatant, and redisperse the precipitate in 0.27 mmol / mL hexadecyltrimethylammonium chloride solution. Then, add 1.67 mmol / mL silver nitrate solution and 3.33 mmol / mL L-ascorbic acid solution sequentially and mix well. Heat the reaction solution in a 65℃ water bath for 4 h. After the reaction is complete, centrifuge the reaction solution at 5000 rpm for 10 min, discard the supernatant, and redisperse the lower precipitate. The gold nanoparticles were dispersed in a 0.25 mmol / mL hexadecyltrimethylammonium bromide solution and allowed to stand in a 30°C water bath for 4 hours. The supernatant was then gently poured off, leaving the precipitate at the bottom. The precipitate was dispersed in 100 mL of deionized water. 10 mL of concentrated hydrogen peroxide and 10 mL of concentrated ammonia were added sequentially, and the mixture was shaken for 30 seconds until the solution became clear. Then, 0.01 mol / mL hexadecyltrimethylammonium bromide solution was added, and the mixture was centrifuged at 9000 rpm for 10 min. After washing, uniform gold nanoparticles were obtained. (4) Take 0.01 mol / mL of the gold nanobipyramid obtained in step (3) and disperse it in a 0.04 mol / mL hexadecyltrimethylammonium chloride solution. Then add 1 mol / mL silver nitrate and 20 mol / mL ascorbic acid solution to obtain a mixed solution. Place the mixed solution in a constant temperature air shaker at 60℃ and 100 rpm and react for 4.5 h. Then centrifuge at 6000 rpm for 10 min. The obtained precipitate is redispersed in a 1.5 mmol / mL hexadecyltrimethylammonium bromide solution. Then add 50 μl of a solution containing 1 mM chloroplatinic acid and 0.01 M L-ascorbic acid. Let it stand at room temperature for 12 h. Then centrifuge at 3500-5000 rpm for 10 min. The obtained precipitate is redispersed in water for storage to obtain Pt-loaded gold nanobipyramid. (5) Prepare a dispersion of gold nanobipyramidal loaded with Pt at a concentration of 5 mg / mL. Drop 50 μL of the dispersion onto pure titanium and then rotate at 1000 rpm for 3 s and 3000 rpm for 30 s to complete one film deposition. Repeat the process 5 times at the same speed. After rinsing with deionized water multiple times, vacuum dry to obtain Ti / Au / Pt material. (6) Soak Ti / Au / Pt in a 2 mg / mL RGDC peptide solution at room temperature for 12 h, then rinse repeatedly with deionized water to remove unreacted RGDC peptide solution, and dry to obtain the final product.
Citation Information
Patent Citations
Preparation method of gold nano bipyramid and application of gold nano bipyramid in optical fiber biosensing
CN117259775A
KR20210125928A